2007
DOI: 10.1175/jpo3058.1
|View full text |Cite
|
Sign up to set email alerts
|

Did the Thermocline Deepen in the California Current after the 1976/77 Climate Regime Shift?

Abstract: The 55-yr California Cooperative Oceanic Fisheries Investigations (CalCOFI) dataset in the southern California Current reveals a significant surface-intensified warming and stratification (buoyancy frequency) change across the 1976/77 climate regime shift. However, the average depth of the thermocline, defined as the maximum gradient of temperature, did not change significantly across the regime shift. The maximumgradient criterion for thermocline depth may be more appropriate than following an isotherm becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Collie, et al [19] pointed out that smooth, abrupt, and discontinuous shifts can be identified on the basis of different patterns in the relationship between the response of an ecosystem variable (typically biological) and some external forcing. Kim, et al [20] demonstrated that specific parameters such as nitrogen levels, upwelling, and thermocline depth can be associ-ated with regime shifts. Aebisher, Coulson and Colebrook [21] discussed how temperature and wind stress variations affect plankton production which can propagate up the food chain and impact fish populations.…”
Section: Discussionmentioning
confidence: 99%
“…Collie, et al [19] pointed out that smooth, abrupt, and discontinuous shifts can be identified on the basis of different patterns in the relationship between the response of an ecosystem variable (typically biological) and some external forcing. Kim, et al [20] demonstrated that specific parameters such as nitrogen levels, upwelling, and thermocline depth can be associ-ated with regime shifts. Aebisher, Coulson and Colebrook [21] discussed how temperature and wind stress variations affect plankton production which can propagate up the food chain and impact fish populations.…”
Section: Discussionmentioning
confidence: 99%
“…For calculating the water column properties (buoyancy frequency and heat content), only data from lines 80 and 90 were used, because vertical profiles are less complete compared with surface data, particularly in the early period. To minimize spatial aliasing, each profile was interpolated by a piecewise cubic spline method to 1 m resolution (Kim & Miller, 2007). With these interpolated data, the pycnocline depth for each profile was calculated as the depth with the maximum vertical gradient of density.…”
Section: Methodsmentioning
confidence: 99%
“…Collie et al (2004) pointed out that smooth, abrupt and discontinuous shifts can be identified on the basis of different patterns in the relationship between the response of an ecosystem variable (typically biological) and some external forcing. Kim and Miller (2007) demonstrated that specific parameters such as nitrogen levels, upwelling and thermocline depth can be associated with regime shifts. Aebisher et al (1990) discussed how temperature and wind stress variations affect plankton production which can propagate up the food chain and affect fish populations.…”
Section: Discussionmentioning
confidence: 99%